Metabolic consequences of ß-alanine supplementation during exhaustive supramaximal cycling and 4000-m time-trial performance - Bellinger, P. M.; Minahan, C. L. (Applied Physiology, Nutrition, and Metabolism, 2016)
The present study investigated the effects of ß-alanine supplementation on the resultant blood acidosis, lactate accumulation, and energy provision during supramaximal-intensity cycling, as well as the aerobic and anaerobic contribution to power output during a 4000-m cycling time trial (TT). Seventeen trained cyclists (maximal oxygen uptake = 4.47 ± 0.55 L·min-1) were administered 6.4 g of ß-alanine (n = 9) or placebo (n = 8) daily for 4 weeks. Participants performed a supramaximal cycling test to exhaustion (equivalent to 120% maximal oxygen uptake) before (PreExh) and after (PostExh) the 4-week supplementation period, as well as an additional postsupplementation supramaximal cycling test identical in duration and power output to PreExh (PostMatch). Anaerobic capacity was quantified and blood pH, lactate, and bicarbonate concentrations were measured pre-, immediately post-, and 5 min postexercise. Subjects also performed a 4000-m cycling TT before and after supplementation while the aerobic and anaerobic contributions to power output were quantified. ß-Alanine supplementation increased time to exhaustion (+12.8 ± 8.2 s; P = 0.041) and anaerobic capacity (+1.1 ± 0.7 kJ; P = 0.048) in PostExh compared with PreExh. Performance time in the 4000-m TT was reduced following ß-alanine supplementation (-6.3 ± 4.6 s; P = 0.034) and the mean anaerobic power output was likely to be greater (+6.2 ± 4.5 W; P = 0.035). ß-Alanine supplementation increased time to exhaustion concomitant with an augmented anaerobic capacity during supramaximal intensity cycling, which was also mirrored by a meaningful increase in the anaerobic contribution to power output during a 4000-m cycling TT, resulting in an enhanced overall performance.